2013
DOI: 10.1371/journal.pgen.1003588
|View full text |Cite
|
Sign up to set email alerts
|

Alu Elements in ANRIL Non-Coding RNA at Chromosome 9p21 Modulate Atherogenic Cell Functions through Trans-Regulation of Gene Networks

Abstract: The chromosome 9p21 (Chr9p21) locus of coronary artery disease has been identified in the first surge of genome-wide association and is the strongest genetic factor of atherosclerosis known today. Chr9p21 encodes the long non-coding RNA (ncRNA) antisense non-coding RNA in the INK4 locus (ANRIL). ANRIL expression is associated with the Chr9p21 genotype and correlated with atherosclerosis severity. Here, we report on the molecular mechanisms through which ANRIL regulates target-genes in trans, leading to increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
357
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(376 citation statements)
references
References 58 publications
12
357
1
6
Order By: Relevance
“…Zhou et al34 firstly disclosed that ANRIL and related inflammatory factors were up‐regulated within ECs under the stimulation of pathogens, which was mediated by up‐regulated TNF‐α that was caused by NF‐κB signalling. Also ANRIL was capable of binding to PRC‐associated protein (ie, Yin Yang 1) to induce or restrain genetic expressions (eg, IL6 and IL8) that were related with inflammatory responses 35, 36, 37. Thus, it was quite acceptable that ANRIL could act on NF‐κB signalling to induce inflammation, thereby generating CAD‐specific cell activities (Figures 3, 4, 5, 6, 7, 8).…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al34 firstly disclosed that ANRIL and related inflammatory factors were up‐regulated within ECs under the stimulation of pathogens, which was mediated by up‐regulated TNF‐α that was caused by NF‐κB signalling. Also ANRIL was capable of binding to PRC‐associated protein (ie, Yin Yang 1) to induce or restrain genetic expressions (eg, IL6 and IL8) that were related with inflammatory responses 35, 36, 37. Thus, it was quite acceptable that ANRIL could act on NF‐κB signalling to induce inflammation, thereby generating CAD‐specific cell activities (Figures 3, 4, 5, 6, 7, 8).…”
Section: Discussionmentioning
confidence: 99%
“…The chromosome 9p21 locus is a prominent example: whereas initial studies focused on the two genes situated at the locus, CDKN2A and CDKN2B, current studies rather point to radically new disease mechanisms. Indeed, it appears that the risk/non‐risk alleles at the 9p21 locus relate to different isoforms of ANRIL and subsequently to preferred synthesis of non‐circular/circular forms of this long non‐coding RNA, which affect via ribosomal function the expression of multiple genes leading ultimately to opposing effects on cell proliferation and apoptosis (Holdt et al , 2010, 2013). …”
Section: Genome‐wide Association Studies In Coronary Artery Disease Amentioning
confidence: 99%
“…Katharina et al 51) found that MALAT1 silencing by siRNA or LNA GapmeRs induced a phenotype switch of the endothelial cells from a proliferation state to a promigratory state. This type of phenotype switch results in a block in vessel outgrowth cells and tissues such as SMCs, ECs, monocytederived macrophages, and RNA samples extracted from carotid and arterectomy 41) . Moreover, the severity of atherosclerosis with ANRIL expression has been described 39,42) .…”
Section: Long Noncoding Rnas Regulate the Function Of Ecsmentioning
confidence: 99%
“…Moreover, Holdt et al found that Alu motifs are essential for the pro-atherogenic functions of ANRIL. ANRIL regulates target genes through the Alu motifs located in ANRIL and the promoters of target-genes resulting in increased cell proliferation, cell adhesion, and decreased apoptosis, which all play critical roles in the process of atherosclerosis 41) .…”
Section: Long Noncoding Rnas Regulate the Function Of Ecsmentioning
confidence: 99%